2015
DOI: 10.3945/jn.114.204065
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A Kinetics in Neonatal Rats vs. Adult Rats: Comparisons from Model-Based Compartmental Analysis,

Abstract: A critical role for vitamin A (VA) in development is well established, but still relatively little is known about whole-body VA metabolism in early postnatal life. Recently, methods of mathematical modeling have begun to shed light on retinol kinetics in the postnatal growth period and on the effect of retinoid supplementation on retinol kinetics. Comparison of kinetic parameters from tracer studies in neonatal rats with those previously determined in models of VA metabolism in the adult suggests both similari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 45 publications
0
16
0
1
Order By: Relevance
“…The preliminary findings of these studies indicate that, compared with adult rats in a similar VA status, the extrahepatic tissues in neonates store relatively little VA (13% compared with 44% in adult rats) (12), despite a higher proportion of retinyl esters (REs) being acquired by these tissues (40% compared with 25%) (13). VA supplementation increased the concentration of retinol in most extrahepatic organs, but only transiently (for w1 d) (12), suggesting that the extrahepatic tissues in neonates may have a limited retinol storage capacity.…”
Section: Introductionmentioning
confidence: 99%
“…The preliminary findings of these studies indicate that, compared with adult rats in a similar VA status, the extrahepatic tissues in neonates store relatively little VA (13% compared with 44% in adult rats) (12), despite a higher proportion of retinyl esters (REs) being acquired by these tissues (40% compared with 25%) (13). VA supplementation increased the concentration of retinol in most extrahepatic organs, but only transiently (for w1 d) (12), suggesting that the extrahepatic tissues in neonates may have a limited retinol storage capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Model-based compartmental analysis [specifically, the Simulation, Analysis and Modeling software (WinSAAM; http://www.WinSAAM.org ) ( 1 )] has been productively used to describe and quantitate retinol kinetics in rats over the past 35 y [see reference 2 for a review as well as Tan et al ( 3 )]. This approach has generated unique and important insights into whole-body vitamin A metabolism, including the fact that there is extensive recycling of retinol among plasma and tissues before irreversible utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we aimed to examine the concentration and mass of retinol in tissues that have been relatively unexplored from the perspective of VA metabolism, such as brain, skin, white adipose tissue (WAT), and brown adipose tissue (BAT). Previous studies have shown that neonates store a greater proportion (51% compared with 44%) of the whole-body VA mass than adult rats in tissues other than the liver, which is the main VA storage organ in VA-sufficient rodents (13). Moreover, a single dose of VA admixed with retinoic acid (VARA) stimulated the uptake of VA by extrahepatic tissues, especially the carcass and intestine, which together acquired ;75% of the recently ingested VA (14).…”
Section: Introductionmentioning
confidence: 99%